Na+ ,K /H+ antiporters regulate the pH of endoplasmic reticulum and auxin-mediated development - Fan, Ligang; Zhao, Lei; Hu, Wei; Li, Weina; Novák, Ondřej; Strnad, Miroslav; Simon, Sibu; Friml, Jiří; Shen, Jinbo; Jiang, Liwen; Qiu, Quan-Sheng (Plant, cell and environment, 2018)
AtNHX5 and AtNHX6 are endosomal Na+ ,K+ /H+ antiporters that are critical for growth and development in Arabidopsis, but the mechanism behind their action remains unknown. Here, we report that AtNHX5 and AtNHX6, functioning as H+ leak, control auxin homeostasis and auxin-mediated development. We found that nhx5 nhx6 exhibited growth variations of auxin-related defects. We further showed that nhx5 nhx6 was affected in auxin homeostasis. Genetic analysis showed that AtNHX5 and AtNHX6 were required for the function of the endoplasmic reticulum (ER)-localized auxin transporter PIN5. Although AtNHX5 and AtNHX6 were colocalized with PIN5 at ER, they did not interact directly. Instead, the conserved acidic residues in AtNHX5 and AtNHX6, which are essential for exchange activity, were required for PIN5 function. AtNHX5 and AtNHX6 regulated the pH in ER. Overall, AtNHX5 and AtNHX6 may regulate auxin transport across the ER via the pH gradient created by their transport activity. H+ -leak pathway provides a fine-tuning mechanism that controls cellular auxin fluxes.
Keywords: homeostáza; Immunoprecipitation; Arabidopsis Proteins; Hydrogen-Ion Concentration; Membrane Transport Proteins; membránové transportní proteiny; Indoleacetic Acids; imunoprecipitace; Endoplasmic Reticulum; Homeostasis; proteiny huseníčku; rostlinné geny; kyseliny indoloctové; Sodium-Hydrogen Exchangers; Na(+)-H(+) antiport; Arabidopsis; promotorové oblasti (genetika); Promoter Regions, Genetic; endoplazmatické retikulum; koncentrace vodíkových iontů; Genes, Plant